DOI: 10.11606/d.23.2010.tde-09062011-110725
|View full text |Cite
|
Sign up to set email alerts
|

Cirurgia de terceiros molares: avaliação da dor, edema, qualidade de vida e variações conforme posição dental

Abstract: Third molar extraction surgery is widely performed with several indications. Pain and swelling prevalence are usual after surgery with potential effects on patients quality of life. Our primary aim was to evaluate the pain, swelling and quality of life after third molar tooth extraction surgery and the effects according to its original position. We performed an interventional prospective study within 86 patients whom preoperative planning is removal of two third molar teeth from the same side at one-time proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
2

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 62 publications
(245 reference statements)
1
1
2
Order By: Relevance
“…The female patients (25%) were more likely to have this complication compared to patients who reported edema (45%), but half of male patients reported facial swelling. In contrast to the study by Negreiros [7] it was observed a higher swelling index in male patients.…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…The female patients (25%) were more likely to have this complication compared to patients who reported edema (45%), but half of male patients reported facial swelling. In contrast to the study by Negreiros [7] it was observed a higher swelling index in male patients.…”
Section: Discussioncontrasting
confidence: 98%
“…The facial swelling was reported by 45% of the patients, relating this data to the ages of the patients, it was observed that 47% of younger patients and 50% of adults reported facial swelling, showing a small variation in age, which shows that there were no correlations between patient age and the appearance of facial swelling, coinciding with study by Negreiros [7], where there was no relationship between age and facial swelling appearance. Differently from this study, Kim et al [18] observed that age is the main factor for the occurrence of facial swelling and Yussa and Sugiura [19] showed that patients older than 40 years had moreedema.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations